Description of the Al-Qur'an Tahfiidz Learning Method - Marliana, Rani; Chotimah, Fitriani Chusnul (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this research is to explain the Al-Qur'an tahfiidz learning method used in the Huffaadzil Qur'an Fadllulloh Islamic Boarding School in Kuripan Kidul, Kesugihan, Cilacap. This study aims to understand and describe the learning process of tahfiidz Al-Qur'an at the Islamic boarding school, including the stages of memorization, the methods used, and the level of learning. Methodology: The type of research used is field research (Field Research) data collection is carried out directly at the research location, and this research is classified as descriptive research, namely research that is directed to provide symptoms, facts, or events in a systematic and accurate manner. about the characteristics of a particular population or area. Main Findings: The Al-Qur'an tahfidz learning method is a strategy used by students to memorize the Al-Qur'an correctly and correctly. The goal is for them to always remember and be able to pronounce the verses of the Qur'an without looking directly at the Mushaf. Novelty/Originality of this study: In memorizing there needs to be a special method so that memorization is easy and the time used for memorizing is relatively short. For students who are tenacious and diligent by applying the method as above and complying with all existing regulations, and always memorizing it repeatedly. So with approximately 2 to 3 years you can finish memorizing the Al-Qur'an.